Record of genus Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae; Copiphorini) and description of one new species from India - Farooqi, Mohd Kaleemullah; Usmani, Mohd Kamil (Zootaxa, 2018)
The study deals with one new record of genus Xestophrys Redtenbacher, 1891 (Conocephalinae: Copiphorinae) and one new species from India, and provides species descriptions and illustrations of the male. All type specimens are deposited in the Zoology Museum, Aligarh Muslim University, India.